2006
DOI: 10.1158/1078-0432.ccr-05-2387
|View full text |Cite
|
Sign up to set email alerts
|

N-Cadherin as a Novel Prognostic Marker of Progression in Superficial Urothelial Tumors

Abstract: Purpose: Loss of intercellular adhesion and increased cell motility promote tumor cell invasion and spreading. In bladder cancer, loss or reduced E-cadherin expression has been associated with poor survival, and aberrant expression of N-cadherin has been associated with the invasive phenotype of bladder carcinoma cells. The purpose of this study was to investigate whether N-cadherin expression was associated with the bladder tumor progression. Experimental Design: E-cadherin and N-cadherin expression was evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
74
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 45 publications
9
74
0
1
Order By: Relevance
“…Inversely, in poorly differentiated T24 cells, E-cadherin is absent and replaced by N-cadherin. 20 On the other hand, coregulator proteins can dramatically influence the activity of nuclear receptors and other transcription factors, thereby influencing cell fate. 38 RT4 cells could be deficient for a specific PPARa and g coactivator or characterized by the overexpression of a corepressor protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inversely, in poorly differentiated T24 cells, E-cadherin is absent and replaced by N-cadherin. 20 On the other hand, coregulator proteins can dramatically influence the activity of nuclear receptors and other transcription factors, thereby influencing cell fate. 38 RT4 cells could be deficient for a specific PPARa and g coactivator or characterized by the overexpression of a corepressor protein.…”
Section: Discussionmentioning
confidence: 99%
“…We chose as reference a non-invasive low-grade pTa tumor expressing the epithelial marker E-cadherin but not the mesenchymal marker Ncadherin. 19,20 The A-FABP mRNA level detected in this tumor was used as reference and set at 100% relative expression. Of 9 pTa tumors, 6 cases (66.6%) presented a high A-FABP expression.…”
Section: Association Of Decreased A-fabp Mrna Expression With High Stmentioning
confidence: 99%
“…(12,13) This phenomenon is correlated with the acquisition of invasiveness and metastatic potential by the cancer cells. Cadherin switching has been observed in biopsies from a wide range of types of cancers, including melanoma, breast, and prostate cancers, (12) bladder carcinoma, (14) some types of ovarian (15) and gastric carcinomas, (16,17) and adrenal tumors. (18) N-cadherin promotes tumor cell survival, migration, and invasion, and high level expression is often associated with a poor prognosis.…”
mentioning
confidence: 99%
“…(17)(18)(19) From the aforementioned results it could be suggested that immunostaining of N-Cadherin may play an important role in the diagnosis and prediction of the biological behavior of different histopathological types of PTC. In addition it can potentially be used for differential diagnosis between PTC and MNG and for prediction of synchronous metastatic existence.…”
Section: Discussionmentioning
confidence: 99%